A small portion of plastid transcripts is polyadenylated in the flagellate Euglena gracilis - Záhonová, Kristína; Hadariová, Lucia; Vacula, Rostislav; Yurchenko, Vyacheslav; Eliáš, Marek; Krajčovič, Juraj; Vesteg, Matej (FEBS letters, 2014)
Euglena gracilis possesses secondary plastids of green algal origin. In this study, E. gracilis expressed sequence tags (ESTs) derived from polyA-selected mRNA were searched and several ESTs corresponding to plastid genes were found. PCR experiments failed to detect SL sequence at the 5'-end of any of these transcripts, suggesting plastid origin of these polyadenylated molecules. Quantitative PCR experiments confirmed that polyadenylation of transcripts occurs in the Euglena plastids. Such transcripts have been previously observed in primary plastids of plants and algae as low-abundance intermediates of transcript degradation. Our results suggest that a similar mechanism exists in secondary plastids.
Keywords: messenger RNA; Genome, Plastid; Polyadenylation; exprimované sekvenční adresy; Quantitative PCR; Euglenozoa; Plastid; plastidy; Plastids; RNA, Messenger; protozoální geny; genom plastidový; Genes, Protozoan; Trans-splicing; Expressed Sequence Tags; Euglena gracilis; RNA protozoální; EST; polyadenylace; RNA, Protozoan